2022
DOI: 10.3892/mco.2022.2508
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a patient‑derived mucoepidermoid carcinoma cell line with the CRTC1‑MAML2 fusion gene

Abstract: Mucoepidermoid carcinoma (MEC) is the most common malignant tumor of the major and minor salivary glands. Surgical resection is the only curative treatment and there is no effective post-operative therapy for MEC. The present study reports an Institutional Review Board-approved case of a 45-year-old Japanese female diagnosed with low-grade MEC in the hard palate. Radical resection, supraomohyoid neck dissection and antero-lateral thigh flap reconstruction was performed. A MEC cell line was then established fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…SGCs are among the most complex head and neck tumors due to the heterogeneity of their population cells ( 33 ), and that makes them challenging to treat. In general, surgery is the main treatment option with curative intent of early-stage SGCs ( 7 ), as observed in our findings, in which 27.7% of the cases were previously treated by surgical resections. In addition, a review by Sahara et al ., 2021 showed that radiation therapy also has a positive effect on local disease control, but its effect on prolonging overall survival is unclear.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…SGCs are among the most complex head and neck tumors due to the heterogeneity of their population cells ( 33 ), and that makes them challenging to treat. In general, surgery is the main treatment option with curative intent of early-stage SGCs ( 7 ), as observed in our findings, in which 27.7% of the cases were previously treated by surgical resections. In addition, a review by Sahara et al ., 2021 showed that radiation therapy also has a positive effect on local disease control, but its effect on prolonging overall survival is unclear.…”
Section: Discussionsupporting
confidence: 73%
“…Currently, the role of systemic therapies in SGCs is palliative, and generally indicated in the advanced/metastatic setting, with low (< 10%) response rates for cytotoxic agents. In addition, a few patients may derive clinical benefits from hormonal therapies, anti-angiogenics, and immunotherapy ( 4 - 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the established cell lines in this study were derived from a high-grade case. MEC cell lines were previously established from low- (HCM-MEC010) [ 22 ], intermediate- (UM-HMC-1, UM-HMC-2, and UM-HMC-3A, B) [ 23 ], or high-grade cases (UT-MUC-1 and HTB-41) [ 24 , 25 ]. H292 and H3118 are also MEC cell lines [ 25 , 26 ]; however, the histological grades of the original tumors have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Each decision can be seen as a component that contributes to a result in an overarching testing and refuting framework, where some results will be essential and others are considered non-contributory [73][74][75]. In addition, certain biomarkers may have multiple functions (e.g., high-risk HPV testing or mismatch repair assessment) that can provide information about the pathogenesis or have diagnostic implications in some settings, but allow for prognostic or even enable therapeutic decision-making in other settings [28,[76][77][78]. Aside from testing, there are utilization patterns, turn-around time pressures, daily case loads, local availability of certain tests, or even intellectual traditions that contribute in various proportions to the final diagnosis and thereby to the overarching diagnostic test performance of the pathologist or practice.…”
Section: Discussionmentioning
confidence: 99%